A real-time wavelet-based video compression approach to intelligent video surveillance systems. (16th January 2006) - Wu, Bing-Fei; Chen, Yen-Lin; Chen, Chao-Jung; Chiu, Chung-Cheng; , Chorng-Yann Su
This work presents a wavelet-based approach to compressing video, with high speed, high image quality and high compression ratio. Using the sequential characteristics of surveillance images, this method applies the low-complexity zero-tree coding, which costs low memory, to develop an algorithm for encoding and decoding video, which greatly improves the speeds of compression and decompression and maintains images of high quality. The method provides good quality and smoothness even under multi channel surveillance, and so is of great value to companies that develop multi-channel surveillance systems. The ActiveX technique is used to implement the algorithm to take advantage of multimedia, the internet and visual rapid-application-development. The versatile and intelligent surveillance system includes peripheral computer hardware and mobile communication. Incorporating IA, this system is not just a surveillance system but is, rather, an intelligent home manager that can control electronic appliances, video/audio systems and home security in an 'e-Home'.